Assessment of the subjective well-being of undergraduate pharmacy students in the University of the Philippines - Divino, Marielle Josette R.​; Policarpio, Mica Anna B.​; Valerio, Claire Louise A.​
Young adulthood is an age of intellectual and social development, self-discovery, and emerging independence. It is the point in one's life where overall health and well-being are at their most vulnerable state. Among university students, those of healthcare professions are found to have higher and more harmful levels of distress. Specifically, pharmacy students have more cases of depression and suicidal thoughts, and lower subjective well-being (SWB) scores. SWB describes a persons's cognitive and affective evaluations of his or her life. This study described the SWB of undergraduate pharmacy students in the University of the Philippines Manila and its association with demographic characteristics, social relationships, and academic functioning. One hundred sixty-one (161) students participated in the study which utilizes a descriptive cross-sectional design using a paper and pen survey. Results revealed that students had an average subjective well-being score of 23.87. They were slightly satisfied (x=4.36) with life, had lower positive affect (x=3.0<3.3) and higher negative affect (x=2.78>1.74). Among the different variables tested for association, social relationships; specifically, relationship with family (p<0.0001) and significant other and academic self-perception (p<0.0001) were found to be significant predictors of SWB. Of the seven dimensions of academic functioning, five were found to be significantly related to SWB.